Blockchain Based Analytical Bug Tracking in Software Engineering - V. M. Subramanyam (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This article examines a blockchain-based bug tracking system in detail, focusing on its four main components: the Blockchain Platform, the Consensus Mechanism (also known as Proof of Work, PoW), the Data Structure, and Smart Contracts. To improve the efficiency, security, and transparency of bug tracking in software development, we use mathematical models to dissect the operational framework and functionalities that underpin this cutting-edge system. The Blockchain Platform is the foundational layer. It stores data in multiple locations, cannot be changed, and provides a secure environment for fixing software bugs. We use mathematical abstractions to demonstrate how the blockchain is put together, emphasizing the importance of cryptographic hashes in maintaining data integrity and connecting blocks. People pay close attention to the Consensus Mechanism, particularly Proof of Work (PoW), because it is so important for verifying transactions and maintaining the blockchain's integrity. Using a mathematical model, we demonstrate how Proof of Work (PoW) prevents bad behavior while keeping the network safe and democratic by requiring work to be done on a computer to add blocks. The Data Structure module is examined using a model that depicts how bug reports are stored and found on the blockchain. This model demonstrates the efficiency of storing bug reports as transactions, which allows for quick access and unchangeable record-keeping. People associate smart contracts with self-running programs that manage permissions, automate workflows, and provide incentives for reporting bugs. Mathematical models are used to demonstrate how these contracts' conditions and actions are documented, emphasizing their importance in automating tasks and improving system reliability. This article uses mathematical modeling to provide a clear and structured understanding of a blockchain-based bug tracking system and demonstrate how it could change the way bugs are tracked by leveraging blockchain technology's strengths.